Environmental Enteric Dysfunction is Associated with Altered Bile Acid Metabolism - Semba, Richard D. (J Pediatr Gastroenterol Nutr, 2017)
OBJECTIVES: Environmental enteric dysfunction (EED), a clinically asymptomatic condition characterized by inflammation of the small bowel mucosa, villous atrophy, and increased gut permeability, is common among children in developing countries. Because of abnormal gut mucosa and altered gut microbiome, EED could potentially affect the metabolism and enterohepatic circulation of bile acids. METHODS: In 313 children, aged 12–59 months, EED was assessed by the dual sugar absorption test. Serum bile acids were measured using stable-isotope liquid chromatography-tandem mass spectrometry. RESULTS: In the overall study population, serum cholic acid and chenodeoxycholic acid were lower while glycocholic acid, taurodeoxycholic acid, glycodeoxycholic acid, glycolithocholic acid, and glycoursodeoxycholic acid were significantly higher at older ages. Independent of age, serum taurochenodeoxycholic acid, tauromuricholic acid, and glycoursodeoxycholic acid were significantly different between 244 children with and 69 children without EED. Total serum bile acids (median, interquartile range) were 4.51 (2.45, 7.51) and 5.10 (3.32, 9.01) µmol/L in children with and without EED, respectively (age-adjusted, P=0.0009). The proportion of bile acids conjugated with taurine instead of glycine was higher in children with EED (P < 0.0001). CONCLUSIONS: EED is associated with altered bile acid metabolism in young children in rural Malawi. Further work is needed to determine the generalizability of these findings in other study populations.